Paradoks Kebahagiaan Dalam Pembangunan: Studi Regresi Data Panel Faktor Ekonomi dan Kesehatan di Negara-Negara Asia Timur - Veranika Nabila; Zulfanetti .; Etik Umiyati; Siti Hodijah; Nurhayani . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the development of factors affecting the level of happiness in East Asian countries, namely Economic Growth, Unemployment, Education (Average Years of Schooling), Per Capita Income, and Health (Life Expectancy). The study employs descriptive analysis and panel data regression using the Fixed Effect Model (FEM) with secondary data from six East Asian countries Taiwan, Japan, South Korea, China, Mongolia, and Hongk ong covering the period 2014–2023. The results show that Economic Growth and Unemployment have a positive but insignificant effect on the Happiness Index, Education has a negative and significant effect, Per Capita Income has a positive and significant effect, while Health has a positive but insignificant effect. Based on the individual effects, Taiwan has the highest level of happiness, while Hongkong has the lowest due to high social and political pressures. Overall, development in East Asia has not yet fully improved happiness evenly across countries, indicating the need for policies focusing on social welfare and quality of life.